(3GdJYde GdPGJj aj YUQ GdeYdheGJs - (3GdCMeO, Ceds ((3HjQhJs (3eDSSI GdQSGdIs, 2002)
(3GSJWGY GdEfSGf YHQ JGQjNg GdWhjd Cf jJZdH Ydi eG jYJQVg ef UYhHGJ, heG jhGLgg ef CReGJ hJMOjGJ HaVd bOQJg Ydi GdJZjjQ, hbGHdjJg ddJZjQ, hGSJKeGQ eG dOjg ef bOQGJ hWGbGJ, hHaVd bOQJg GddGeMOhOI Ydi GdJYde HUhQI YGeI, hGdJYde GdPGJj Ydi hLg GdNUhU(B. (3hGdMb Cf GdJYde GdPGJj HTcdg GdChdj GdHSjW, bOje bOe GdEfSGf, abO cGf GdSHjd GdhMjO dOjg dehGLgI bhi GdWHjYI hbgQgG, hGdSjWQI YdjgG, hGdSHjd Edi EVaGA GdWGHY GdYbdGfj Ydi Sdhc GdaQGO hGdLeGYGJ(B. (3dcf JfGej GdNHQjI GdGLJeGYjI hJfhYgG aj eNJda GdejGOjf, LYd CSGdjH GdJYde GdPGJj GdJj JhqUd EdjgG GdEfSGf aj aLQ MVGQJg bGUQI Ydi GSJjYGH gPg GdNHQI, eeG Ndb MGLI eGSI Edi hLhO eDSSGJ GLJeGYjI eJNUUI JYjfg Ydi GdbjGe HeKd gPg GdegeI, hgcPG hLOJ GdeOQSI efP eFGJ GdSfjf, ceDSSI JYdjejI, JKbjajI, GLJeGYjI, CNdGbjI(B... (3GdN hbO GSJWGYJ Cf JJWhQ, hJWhQ WQGFbgG hCSGdjH YedgG YHQ GdYUhQ, hZdi aJQI djSJ HHYjOI cGfJ JYjT YUQgG GdPgHj(B. (3dcf GdJZjjQGJ GdTGedI hGdYejbI GdJj WQCJ Ydi cGaI fXe GdeLJeY heDSSGJg, haj YOGOgG GdeOQSI, LYdJ gPg GdCNjQI JFf JMJ hWCI GdegGe GdLSGe GdehcdI EdjgG(B. (3hef fGMjI KGfjI, aEf GdXQha GdJj jeQ gG GdYGde Gdjhe, MGdJ hMhd Hjf GdeJYde hMSf eJGHYJg GdOQGSI GdfXGejI aj GdeOQSI, Ch JMbjb GdaGFOI GdeQLhI ef gPg GdOQGSI, eeG CcSH GdJYdje GdPGJj HYOkG LOjOkG, hCQZe GdYdeGA hGdeQHjf Ydi GdJacjQ, ef CLd EjLGO SHd hWQGFb JSqQY YedjI GdJYde hGdJYdje, hJYqhV GdhbJ GdegOhQ hGdVGFY bSQkG aj Xd GdXQha GdJYdjejI GdJbdjOjI GdSGFOI, HMjK jDOj Pdc cdg Edi OYe GdeOQSI hJYRjR LghOgG hJecjfgG ef GSJFfGa OhQgG GdJGQjNj(B. (3hdYd ef Cge eG JhUd Edjg GdYdeGA aj gPG GdeLGd, gh GdJCcjO Ydi eG cGf GdEfSGf bO HOC Hg MjGJg, Ch hgh GdJYde GdPGJj, HMjK jSJajO eeG eQJ Hg GdeOQSI ef JLGQH hNHQGJ ZfjI hbjeI, heG CfLRJg GdMVGQI ef WQGFb hCSGdjH YdejI eJYOOI(B. (3heY RjGOI MLe GdeYdheGJ hfhYgG, CUHM ef GdeJYPQ Ydi GdeOQSI YehekG, hGdeOQSI GdYQHjI HUhQI NGUI, ehGLgI gPG GdJOab GdeYdheGJj HeaQOgG, dPG aEf GdWQjbI GdefGSHI ddJUOj dgPg GdeTcdI Jcef aj Cf fYqde GdeJYqde cja jJYde HfaSg hab WQGFb hGJLGgGJ JQHhjI faSjI eJYOOI GdeOGNd, eeG jSgd Ydi GdeOQSI GdbjGe HGdCOhGQ GdedbGI Ydi YGJbgG, hjJjM GdeLGd ddeJYde GdQGZH hGdcaD Cf jhGUd OQGSGJg hGSJbUGAGJg eYJeOkG Ydi PGJg(B. (3hdbO dbj gPG GdGJLGg SfOkG dg aj JbQjQ GddLfI GdOhdjI ddjhfjSch, GdPj jDcO Ydi Cfg(B: "(3jfHZj Cf jchf GdeHOC GdPj jbhe Ydjg Cj fXGe JQHhj, gh JQcjR GdfTGW cdg Ydi GdeJYqde(B". (3dbO ZOG GdJYqde GdPGJj EMOi GdGSJQGJjLjGJ GdQFjSI GdQGejI Edi JWhjQ GdCfXeI GdJQHhjI hJMOjKgG aj LejY CfMGA GdYGde(B. (3hef gfG JCJj CgejI gPG GdcJGH GdPj jWQM Ydi HSGW GdHMK GdJYde GdPGJj aj YUQ GdeYdheGJ eJfGhdkG GdeMGhQ GdJGdjI(B: (3GdCSS GdfaSjI ddJYde GdPGJj, GdeONd GdSdhcj aj GdJYde, GdeONd GdeYQaj aj GdJYde aj GdJYde, ehGRfI Hjf GdeONdjf; GdSdhcj hGdeYQaj aj GdJYde, GdJYdje GdPGJj GdLeGYj, GSJNOGe GdMGShH aj GdJYde hGdJYdje GdPGJjjf, OQGSI JWHjbjI Mhd GdJYdje GdPGJj hab GdeONdjf GdSdhcj hGdeYQaj, YQV hJMdjd heOGNdGJ, GdJUeje GdJLQjHj hJWhjQ GdHQGeL, JWHjb JLQHI GdJYde GdPGJj GdfgGFjI habO GdeNdjf GdSdhcj hGdeYQaI, JMdjd fJGFL GdJbhje GdfgGFj ddJYde GdPGJj hab GdeONdjf GdSdhcj hGdeYQaj, NdGUI GdHMK hebJQMGJg(B.s
(3GdfhY (B: (3cJGHs
Keywords: Auto-apprentissage; Education et la technologie; Self-Learning ICT and Education; (3GdJYde GdPGJj GdJYdje hGdJcfhdhLjGs